Transitioning Pharmacogenomics into the Clinical Setting: Training Future Pharmacists - Frick, Amber; Benton, Cristina S.; Scolaro, Kelly L.; McLaughlin, Jacqueline E.; Bradley, Courtney L.; Suzuki, Oscar T.; Wang, Nan; Wiltshire, Tim (Frontiers in Pharmacology, 2016)
Pharmacogenomics, once hailed as a futuristic approach to pharmacotherapy, has transitioned to clinical implementation. Although logistic and economic limitations to clinical pharmacogenomics are being superseded by external measures such as preemptive genotyping, implementation by clinicians has met resistance, partly due to a lack of education. Pharmacists, with extensive training in pharmacology and pharmacotherapy and accessibility to patients, are ideally suited to champion clinical pharmacogenomics. This study aimed to analyze the outcomes of an innovative pharmacogenomic teaching approach. Second-year student pharmacists enrolled in a required, 15-week pharmaceutical care lab course in 2015 completed educational activities including lectures and small group work focusing on practical pharmacogenomics. Reflecting the current landscape of direct-to-consumer genomic testing, students were offered 23andMe genotyping. Students completed surveys regarding their attitudes and confidence on pharmacogenomics prior to and following the educational intervention. Paired pre- and post-intervention responses were analyzed with McNemar’s test for binary comparisons and the Wilcoxon signed-rank test for Likert items. Responses between genotyped and non-genotyped students were analyzed with Fisher’s exact test for binary comparisons and the Mann-Whitney U-test for Likert items. Responses were analyzed for all student pharmacists who voluntarily completed the pre-intervention survey (N=121, 83% response) and for student pharmacists who completed both pre- and post-intervention surveys (N=39, 27% response). Of those who completed both pre- and post-intervention surveys, 59% obtained genotyping. Student pharmacists demonstrated a significant increase in their knowledge of pharmacogenomic resources (17.9% vs. 56.4%, p<0.0001) and confidence in applying pharmacogenomic information to manage patients’ drug therapy (28.2% vs. 48.7%, p=0.01), particularly if the student had received genotyping. Student pharmacists understanding of the risks and benefits of using personal genome testing services significantly increased (55.3% vs. 86.8%, p=0.001) along with agreement that personal genomics would likely play an important role in their future career (47.4% versus 76.3%, p=0.01), particularly among students who participated in genotyping. The educational intervention, including personal genotyping, was feasible and positively enhanced students’ reflections and attitudes towards pharmacogenomics in a professional pharmacy program.